Impact exercises especially in the development of speed and its relationship with the completion of (200 m) freestyle - Malek Alshok, Ali (Journal of Physical Education, 2008)
Conducted research to identify the impact of special exercises to develop its relationship with speed and completion (200) meters swimming free through the preparation of special exercises and applied research on a sample within the training curriculum for two months and one (3) training modules Week, has been selected sample of the national team pool of young age (13 - 14) years numbered (8) swimmers have been selected intentional manner, divided into two groups, each group (4) the first female swimmer and the other pilot was conducting a test before me at the end of the application method was tested after me. A researcher at the following conclusions: 1 - that the practice of members of the group of pilot exercises on the stomach by a researcher and continue to exercise regularly, had a positive impact on the development and progress with the speed level of achievement. 2 - The use of these exercises in the concluding part of the training unit and consistency with the training of pregnancy had an impact on the physical side of the pool. Recommendations: In the light of research findings and conclusions reached researcher to: 1 - to focus on the application of special exercises in the concluding part of the module. 2 - directing trainers to use these exercises because of its positive influence in the development of physical attributes such as speed and thus bear upgrade sports achievement. 3 - researcher recommends the need for more research and studies using special exercises in the development of other physical attributes and other events in swimming.